1972
DOI: 10.1083/jcb.53.1.66
|View full text |Cite
|
Sign up to set email alerts
|

SEPARATION OF MITOCHONDRIAL MEMBRANES OF NEUROSPORA CRASSA

Abstract: Separation of Neurospora mitochondrial outer membranes from the inner membrane/matrix fraction was effected by digitonin treatment and discontinuous density gradient centrifugation. The solubilization of four isoleucine-valine biosynthetic enzymes was studied as a function of digitonin concentration and time of incubation in the detergent. The kinetics of the appearance of valine biosynthetic function in fractions outside of the inner membrane/matrix fraction, coupled with enzyme solubilization patterns simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Our results also demonstrate that MoIlv6 is localized to the mitochondria and that the conserved domains are not necessary for this localization. Previous studies of fungal Ilv6 proteins have indicated that the precursor proteins maintain a signal peptide targeting ALS to the mitochondria (Cassady et al, 1972;Lee and Duggleby, 2006). The signal peptide is required for mitochondrial localization, and for conidial morphology and infection-related development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also demonstrate that MoIlv6 is localized to the mitochondria and that the conserved domains are not necessary for this localization. Previous studies of fungal Ilv6 proteins have indicated that the precursor proteins maintain a signal peptide targeting ALS to the mitochondria (Cassady et al, 1972;Lee and Duggleby, 2006). The signal peptide is required for mitochondrial localization, and for conidial morphology and infection-related development.…”
Section: Discussionmentioning
confidence: 99%
“…In fungi, the ALS enzyme contains a catalytic subunit of 60-70 kDa and a regulatory subunit that varies in size depending on the species and isoform Duggleby, 1999, 2001). Both the catalytic and regulatory subunits are nuclear encoded and targeted to the mitochondria as a result of the presence of a mitochondrial signal peptide (Cassady et al, 1972;Lee and Duggleby, 2006;Polaina, 1984;Sherman et al, 1974). As no ALS has been identified in animals, inhibitors of ALS, aiming to inhibit the BCAA biosynthetic pathway, have been explored as potential antifungal drug targets (Chipman et al, 1998;Goldstein and McCusker, 2001;McCourt and Duggleby, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, threonine deaminase is apparently cytosolic while most, if not all, of a cell's acetohydroxy acid synthase, acetohydroxy acid isomeroreductase, and dihydroxy acid dehydratase is localized to the mitochondrial matrix (22,80).…”
Section: Neurospora Crassamentioning
confidence: 99%
“…In contrast to the bacterial enzyme, the structure and biochemical properties of AHAS from eucaryotes have not been extensively characterized, and in most cases the enzyme has been studied in crude cell extracts only. Fungal AHAS is localized in the mitochondria ( , ) and plant AHAS in the chloroplast (), although the genes may be found in the nuclear or in the organelle genome ( ). In those cases where it is nuclear-encoded, the enzyme is transported to the appropriate subcellullar compartment.…”
mentioning
confidence: 99%